ACADEMIC EMOTIONS OF MIDDLE SCHOOL STUDENTS LEARNING ENGLISH AFTER THE COVID-19 PANDEMIC: HIGH ACHIEVERS' EXPERIENCES - Hasanah, Uswatun; Setyono, Budi; Ariani, Musli (ELLTER Journal, 2024)
Changes in English language learning experienced by students after the pandemic can elicit a range of academic emotions. These emotional changes can be due to the environment and different learning atmospheres. The existence of these emotional changes will also have an impact on students’ academic achievement. Therefore, this study aims to examine the academic emotions of high-achieving students of junior high school learning English after the Covid-19 pandemic and how they affect students’ effectiveness in learning English. Using a descriptive case study research design to explore students' academic emotions, the research revealed the existence of four types of academic emotions: achievement, epistemic, topic, and social emotions. Each type was accompanied by positive and negative experiences. The positive emotions such as happiness, enjoyment and confidence can be caused by their enthusiasm and interest in learning, which closely related to the achievement obtained. Inversely related to the negative emotions, they tend to feel bad when they do not like something done during offline learning.